Systematic Literature Review (SlR): Characteristics of Millennial Generation Workers - Supriyani, Ani; Yuwana, Yohana Koronka Adi; Lidya, Fatikha Putri; Sahrah , Alimatus (CV. Publikasi Indonesia, 2025)
This study examines the characteristics of millennial workers in Indonesia, focusing on their values, challenges, and needs within a constantly evolving work environment. Millennials, born between 1981 and 1996, are known as